Alpha-momorcharin regulates cytokine expression and induces apoptosis in monocytes. (4th March 2019) - Deng, Nianhua; Sun, Yun; Liu, Mengling; He, Qianchuan; Wang, Ling; Zhang, Yu; Sun, Wenkui; Lei, Ning; Liu, Yang; Luo, Yingxia; Shen, Fubing
Abstract: Background and aim: Alpha-momorcharin (α-MMC) is a type I ribosome-inactivating protein (RIP) that is purified from Momordica charantia . Despite its strong antitumor activities, α-MMC exerts the undesirable immunotoxicity effects of hypersensitivity or immunosuppression. Since α-MMC is a plant protein, its application in vivo can easily induce hypersensitivity, but its immunosuppressive mechanism is still unclear. Materials and methods: The toxicity of α-MMC to peripheral blood cells and the cytokine expression in peripheral blood mononuclear cells (PBMCs) and spleen immune cells were measured in rats. For further confirmation, experiments were performed in vitro with the mononuclear cell line THP-1, B lymphocyte cell line WIL2-S and T lymphocyte cell line Jurkat. Results: High doses of α-MMC (3.0 mg/kg) resulted in weight loss in rats, a decreased percentage of monocytes, and increased percentages of eosinophils and basophils. Both high-dose and low-dose (1.0 mg/kg) α-MMC inhibited cytokine expression in PBMCs and increased cytokine expression in spleen T cells. In in vitro, α-MMC mainly acted on THP-1 cells, with effects including high dose-induced apoptosis and low dose-induced regulation of inhibitory cytokine expression. Conclusions: The action of α-MMC on immune cells mainly affects monocytes, thereby eliciting its immunosuppressive effect. Its mode of action is to guide functional immunosuppressive regulation at low doses and induce apoptosis at high doses. As the monocytes would be recruited into tumor tissues and are polarized into tumor-associated macrophages, the selective cytotoxicity and cytokine release regulation of α-MMC in monocytes may be an important mechanism of its antitumor effects.